1973
DOI: 10.1083/jcb.56.2.487
|View full text |Cite
|
Sign up to set email alerts
|

Dibutyryl Cyclic Adenosine 3' 5' Monophosphate, Sugar Transport, and Regulatory Control of Cell Division in Normal and Transformed Cells

Abstract: Swiss 3T3 cells exhibit contact-regulated cell growth and have a lower ability to transport 2-deoxyglucose than polyoma (Py)-transformed 3T3 cells. Py3T3 cells treated with dibutyryl cyclic adenosine 3'5' monophosphate (dBcAMP) and theophylline have reduced cell growth and transport 2-deoxyglucose at the same rate as normal 3T3 cells. Evidence that the cessation of cell growth and reduced transport abilities in Py3T3 cells does not represent a return to contact-regulated growth comes from the following observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1974
1974
1990
1990

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Thus addition of N6,2'-O-dibutyryl cyclic AMP, particularly with theophylline, to transformed cells has been reported to restore density-dependent inhibition of cell growth (Hsie & Puck, 1971;Sheppard, 1971). However, other workers have found that the inhibition of growth this causes differs from that in dense cultures of normal cells (Paul, 1972;Smets, 1972;Grimes & Schroeder, 1973;Van Wijk et al, 1973). Zacchello et al (1972 reported that the adenylate cyclase activity per mg of cell protein in human diploid fibroblasts increases during growth to confluence.…”
Section: Discussionmentioning
confidence: 93%
“…Thus addition of N6,2'-O-dibutyryl cyclic AMP, particularly with theophylline, to transformed cells has been reported to restore density-dependent inhibition of cell growth (Hsie & Puck, 1971;Sheppard, 1971). However, other workers have found that the inhibition of growth this causes differs from that in dense cultures of normal cells (Paul, 1972;Smets, 1972;Grimes & Schroeder, 1973;Van Wijk et al, 1973). Zacchello et al (1972 reported that the adenylate cyclase activity per mg of cell protein in human diploid fibroblasts increases during growth to confluence.…”
Section: Discussionmentioning
confidence: 93%
“…Theophylline, which elevates intracellular cyclic AMP by blocking its degradation, had a similar growth inhibiting effect. It is known that cyclic AMP regulates growth of certain cells [23,24]. In a parallel study, theophylline similarly depressed the growth of normal fibroblasts (data not shown).…”
Section: Discussionmentioning
confidence: 60%
“…The effects of cyclic AMP on the multiplication oftransformed cells are different from those produced by limiting the concentration of Mg2+. In one case it was reported that the addition of cyclic AMP limits the number of cell generations regardless of the initial density (12), and in another it was reported that growth on solid surfaces is unchanged by cyclic AMP (13 …”
Section: Resultsmentioning
confidence: 99%